Pengaruh Alginat dari Alga Coklat (Sargassum sp) terhadap Penyembuhan Luka Diabetes Melitus pada Tikus yang Diinduksi Streptozotocin - TAUFAN ANTARISKA; NITA PRANITASARI; JUDYA SUKMANA; IRMA ANDRIANI PASARIBU (Universitas Hang Tuah, 2022)
Diabetes mellitus is a degenerative disease which its prevalence increases over time, this disease is often overlooked, thereby increasing complications. Uncontrolled long-term hyperglycemia will cause sensory nerve and blood vessel function disorders. Disruption of the non-healing chronic wound reparation process due to this condition will result in excessive ROS level accompanied by secondary infection, increasing the risk of amputation and death. On the other hand, alginate produced by the cell walls of brown algae (Sargassum sp) is believed to be able to increase the formation of new blood vessels, balance excessive ROS level, and prevent infection at the wound site. This study was conducted to examine the effect of topical alginate on wound healing in diabetic rats. The population in this study includes articles that discuss wounds healing process in diabetic rats induced by streptozotocin (STZ) given alginate therapy. The research sample was obtained from data that had been affixed in 15 international research articles indexed by Scimago from 2016 to 2021. The method used in this study was a literature review. This research took place from May to December 2021.The results of the 15 articles reviewed revealed that alginate could improve wound healing in STZ-induced diabetic rats, this was indicated by decrease in duration of wound closure and inflammation, increase proliferation of epithelial cells and collagen density, and prevent the occurrence of secondary infection at the wound site. Based on these findings, it was concluded that topical administration of alginate had a good effect on the wound healing process of STZ-induced diabetic rats. Keywords: Alginate; diabetic mice; streptozotocin; wound healing